2021
DOI: 10.1186/s12957-021-02268-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating tumour cells and Ki-67 in renal cell carcinoma

Abstract: Background Renal cell carcinoma (RCC) is a common malignant tumour of the genitourinary system. We aimed to analyse the potential value of metastasis-related biomarkers, circulating tumour cells (CTCs) and the proliferative marker Ki-67 in the diagnosis of RCC. Methods Data from 24 laparoscopic radical nephrectomies (RNs) and 17 laparoscopic partial nephrectomies (PNs) were collected in 2018. The numbers and positive rates of CTCs and circulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…The ubiquitination factor E4B (UBE4B) has been extensively explored in ccRCC tumor tissues and cell lines and may act as an oncogene in ccRCC development, apoptosis, and cell proliferation regulation [ 24 ]. Furthermore, degradation and ubiquitination of ARHGEF7, mediated by KLHL2, was observed in ccRCC cell cultures, suggesting the essential role of ubiquitination in the development of ccRCC [ 25 , 26 ]. Likely, ubiquitin-like PHD and RING finger domain 1 (UHRF1) has been reported to promote non-degradative ubiquitination of p53, suppress p53 pathway activation, and p53-dependent apoptosis in ccRCC cells [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitination factor E4B (UBE4B) has been extensively explored in ccRCC tumor tissues and cell lines and may act as an oncogene in ccRCC development, apoptosis, and cell proliferation regulation [ 24 ]. Furthermore, degradation and ubiquitination of ARHGEF7, mediated by KLHL2, was observed in ccRCC cell cultures, suggesting the essential role of ubiquitination in the development of ccRCC [ 25 , 26 ]. Likely, ubiquitin-like PHD and RING finger domain 1 (UHRF1) has been reported to promote non-degradative ubiquitination of p53, suppress p53 pathway activation, and p53-dependent apoptosis in ccRCC cells [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trans-circulatory pathway is one of the most important pathways in RCC metastasis ( 211 ). A metastatic disease is the result of circulating tumor cells (CTCs), a rare subset of tumor-disseminated cells that are shed in the patient's blood.…”
Section: Circulating Tumor Cells and Patient-derived Tumor Organoids:...mentioning
confidence: 99%
“…Driemel et al found that the high expression of EpCAM was common in cancer cells in the proliferation stage, while the low expression of EpCAM inhibited the proliferation of CTCs [27]. Studies have reported low levels of expression of proliferating nuclear antigen Ki-67 in CTCs, suggesting that most CTCs may remain in a dormant state without entering the cell division cycle [28,29]. It has also been found that, several years after primary tumorigenesis, dispersed CTCs and micrometastasis niche can remain dormant for a long time during resection of primary tumors [30].…”
Section: Proliferation and Apoptosis Of Ctcsmentioning
confidence: 99%